2017
DOI: 10.1038/emm.2017.88
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic relocalization of NHERF1 mediates chemotactic migration of ovarian cancer cells toward lysophosphatidic acid stimulation

Abstract: NHERF1/EBP50 (Na+/H+ exchanger regulating factor 1; Ezrin-binding phosphoprotein of 50 kDa) organizes stable protein complexes beneath the apical membrane of polar epithelial cells. By contrast, in cancer cells without any fixed polarity, NHERF1 often localizes in the cytoplasm. The regulation of cytoplasmic NHERF1 and its role in cancer progression remain unclear. In this study, we found that, upon lysophosphatidic acid (LPA) stimulation, cytoplasmic NHERF1 rapidly translocated to the plasma membrane, and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“… 211 Still, it has been reported that LPA might also become a biomarker in vaginal fluid, but only for endometrioid ovarian cancer, being even more sensitive than the classical marker CA125. 212 LPA promotes migration of ovarian cancer cells through different mechanisms/signaling pathways: RhoA/ROCK and Rac1/PAK, 213 CXCL12‑CXCR4, 214 uPA/uPAR, 215 G αi2 /Src/β-pix/Rac, 216 FOXM1, 217 LPAR1, 218 NHERF1/cpERMs, 219 ETS-1, 186 LPAR1/LPAR2/ERM, 220 LPAR2/ERK, LPAR3/ERK, and LPAR6/AKT. 221 LPA has also been implicated in the maintenance of cancer stem cell characteristics through ATX–LPA–LPAR1–AKT1 signaling axis in an autocrine loop.…”
Section: Lpa and Cancermentioning
confidence: 99%
“… 211 Still, it has been reported that LPA might also become a biomarker in vaginal fluid, but only for endometrioid ovarian cancer, being even more sensitive than the classical marker CA125. 212 LPA promotes migration of ovarian cancer cells through different mechanisms/signaling pathways: RhoA/ROCK and Rac1/PAK, 213 CXCL12‑CXCR4, 214 uPA/uPAR, 215 G αi2 /Src/β-pix/Rac, 216 FOXM1, 217 LPAR1, 218 NHERF1/cpERMs, 219 ETS-1, 186 LPAR1/LPAR2/ERM, 220 LPAR2/ERK, LPAR3/ERK, and LPAR6/AKT. 221 LPA has also been implicated in the maintenance of cancer stem cell characteristics through ATX–LPA–LPAR1–AKT1 signaling axis in an autocrine loop.…”
Section: Lpa and Cancermentioning
confidence: 99%
“…Altogether, our data indicate that LPA-mediated GPR35 signaling in macrophages results in a distinct transcriptional profile, characterized by TNF production, which was associated with ERK and NF-KB activation. Given that LPA increases the migration of monocytes, microglia, and ovarian cancer cells (Oh et al, 2017;Plastira et al, 2017;Takeda et al, 2019), we next tested whether LPA acts as a chemoattractant for macrophages. We quantified the migration of WT and Gpr35 KO BMDMs in response to LPA in a transwell migration system, which revealed that Gpr35-deficient BMDMs had reduced migration in response to LPA compared to WT BMDMs (Figure 3F).…”
Section: Lpa Induces Tnf Expression In Macrophages In a Gpr35-dependent Mannermentioning
confidence: 99%
“…EBP50 has various roles in cellular functions of cancer cells, in addition to modulating transporter activity. For example, EBP50 affects cellular proliferation and trafficking [ 16 , 17 ], and oncogene activation [ 18 ]. Therefore, inhibiting EBP50 may have additional effects on cancer cells, depending on their type.…”
Section: Discussionmentioning
confidence: 99%